FACTORS AFFECTING THE AMOUNT OF CREDIT OF BANQUE POUR LE COMMERCE EXTERIEUR LAO PUBLIC - PATHOUMTHONG, Santi; SIPHANTHONG, Bounthavy; PHILASOUK, Thatsapone; PHANTHOULACK, Ounheuan (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The uncertainty of the current situation of Lao and global economies have made difficult for business entrepreneurs struggling with economic issues, the use of modern technology, high competitation, natural disasters and global epedemic, particularly Covid-19 are the major factors contributing to business operators to seek for sources of finances from financial institutions, for instance business bank to strengthen its capacity. Thus, Banque Pour Le Commerce Exterieur Lao Public (BCEL), one of the most best banking sectors in Lao PDR, has played a significant role in providing loans in an attempt to provide banking services and has made an enormous contribution to the socio-economic development of Lao PDR. An investigation of the factors affecting the credit of Banque Pour Le Commerce Exterieur Lao Public(BCEL) via the use of quantitative analysis and secondary data, which were collected from fourth quater of 2011 to the third quarter of 2019 from BCEL financial Report, was applied to test the correlation between factors affecting the amount of fixed deposit of BCEL. To examine these factors, the methods of ordinary least sqaure (OLS) was deployed in order to effectively manage credit management which is considered to benefit a variety of business sectors of the country as they are more likely to accelerate the country’s development leading to graduation from least developed country in the future. The study found that BCEL's credit structure provides medium-term loans at an average of 55.89% of all loans for Trading companies and Services company. The Credit's Capital sources is almost from the deposits at an average of 65.03% of the loans. The majority of the debt structure is performing loans (PL) at an average of 97.96% of total loans and 2.04% of non-performing loans (NPL), which is lower than Bank of the Lao PDR standard set. An analysis also shows that the factors affecting the amount of Credit of BCEL are from the changing of good loan interest rates (AAA Loan), deposits amount, loans amount from other bank and changing of non-performing loans amount and these factors are statistically significant at 99% level of confidence. The result also shows that changing of capital investment amount in the stock market do not affect on the credit mount of BCEL.